Investigating English for Specific Purpose (ESP) Learners’ Perspectives towards Factors Causing Demotivation in ESP Classes - Hotak, Soma; Hekmat, Ali Mohammad; Kamal, Mohammad Mustafa; Rogmal , Shafiullah (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2024)
Abstract This article discusses the importance of motivation in teaching and learning English as a foreign or second language, particularly in the context of English for Specific Purposes (ESP) classes. The study aims to identify demotivating factors affecting ESP learners at Kabul University of Medical Sciences (KUMS) and provide recommendations for improving the quality of English language teaching programs at higher education institutions level. The findings suggest that outdated teaching methods, a lack of relevance to learners' fields of study, and insufficient teachers’ support are one of the main demotivating factors. However, teachers’ enthusiasm and learner autonomy were identified as positive factors that enhance undergraduate students’ motivation. The article, further, recommends that teachers and administrators address the identified demotivating factors and promote positive factors to develop a more motivating and engaging learning environment for ESP learners at KUMS.